2014
DOI: 10.1074/jbc.m114.560979
|View full text |Cite
|
Sign up to set email alerts
|

CREPT/RPRD1B, a Recently Identified Novel Protein Highly Expressed in Tumors, Enhances the β-Catenin·TCF4 Transcriptional Activity in Response to Wnt Signaling

Abstract: Background: CREPT/RPRD1B promotes tumor growth through up-regulating CYCLIN D1 expression. Results: CREPT interacts with ␤-catenin in response to Wnt signaling and enhances the occupancy of ␤-catenin to promoters of Wnt-targeted genes, resulting in an up-regulation of expression. Conclusion: CREPT functions as a co-activator for ␤-catenin⅐TCF4. Significance: CREPT-regulated Wnt signaling implies an oncogenic role in promoting cell proliferation and invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 34 publications
6
61
1
Order By: Relevance
“…These results suggest that mammalian p15RS functions differently from its yeast homolog Rtt103. Intriguingly, the role of p15RS in the regulation of gene transcription also differs from that of CREPT as we observed that CREPT binds to both the promoter and termination region of the CCND1 gene (24) and promotes Wnt signaling (40). However, the differential roles of p15RS and CREPT in regulating gene transcription were not elucidated by partial structural analyses (23,25,27).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…These results suggest that mammalian p15RS functions differently from its yeast homolog Rtt103. Intriguingly, the role of p15RS in the regulation of gene transcription also differs from that of CREPT as we observed that CREPT binds to both the promoter and termination region of the CCND1 gene (24) and promotes Wnt signaling (40). However, the differential roles of p15RS and CREPT in regulating gene transcription were not elucidated by partial structural analyses (23,25,27).…”
Section: Discussionmentioning
confidence: 50%
“…Although yeast Rtt103 was demonstrated to be a gene that favors cell growth (as the double deletion of Rtt103 is synthetic lethal) (39) and human/mouse CREPT promotes tumor cell proliferation (24,40), p15RS was reported to inhibit cell growth as demonstrated by both Liu et al (22) and Chang and co-workers (29). Interestingly, although yeast Rtt103 binds only to the 3Ј-end of genes to regulate transcriptional termination by a mechanism called the Torpedo model, our results indicated that p15RS preferably binds to the promoter regions of the c-MYC and CCDN1 genes as shown here (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, the suggestive association of RPRD1B with docetaxel-induced neuropathy, indicates that other mechanisms may be important. RPRD1B functions as a co-activator of the β-catenin-TCF complex to enhance the transcriptional activity of Wnt signaling (48). Wnt signaling is critical for initial neural cell-fate determination, patterning and synapse formation of sensory neurons of the dorsal root ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…The human gastric adenocarcinoma cell line (MGC803) expressing CREPT stably was applied as positive control [6], and the normal human oral keratinocyte cell line (HOK) as normal control[10, 20, 21]. SCC25, CAL27 and HOK were obtained from the American type culture collection (ATCC).…”
Section: Methodsmentioning
confidence: 99%
“…Similar to cyclin D1, the expression of a series of cell cycle-related factors, such as cyclin E, CDK2, CDK4 and CKD6, are also promoted by CREPT in the same manner [9]. Additionally, recent studies also revealed that CREPT could stabilize the binding of β-catenin/TCF4 complex to the promoters of cyclin D1 and c-Myc, which enforced the effects of Wnt canonical signaling on cell cycle [10]. Besides the enhancement on tumorigenesis, CREPT also plays a critical role in the activation of peripheral T cells, keratinocyte differentiation and metastasis by regulating cell cycle-related genes [11].…”
Section: Introductionmentioning
confidence: 99%